Strain sensor using fiber bragg grating interrogation - Abd Rahim, Mohd Shahrir (2020)
This research aims to focus on analyzing a novel design of strain sensor using Fiber Bragg Grating (FBG) interrogation. Studies on fiber optic sensors reported have mainly focused on FBG wavelength-based monitoring method by using optical spectrum analyzers (OSA). Although FBG has better strain sensitivity measurement, however there have some restriction to monitor by using OSA. The usage of OSA are very costly, bulky and has slow scanning speed. Therefore, research is conducted to design and construct a fully portable, low-cost and low-powered interrogator which is specifically designed to read FBGs within the C-band. An optical strain sensor utilizing reflected light of FBG as input to sagnac loop filter (SLF) is experimentally demonstrated in this work. The proposed SLF has been employed for intensity interrogation of FBG strain sensor where the polarization maintaining fiber (PMF) serves as an edge filter. By monitoring the optical power changes, it is feasible to obtain information that permits strain measurement with a simple and low-cost structure. This work resulted in four milestones. The first is the successful characteristic of strain sensor using FBG 1550nm wavelength. Then, the SLF is characterized using ASE. The output spectrum of SLF is a comb filter and has free spectrum range of 15nm. After that, laser scanning of SLF using TLS is demonstrated. It shows that the optical power is greater than 900μW while the value of R-squared is 0.9931. Finally, by using OSA, the wavelength peak shifts from 1550.088nm to 1550.252nm when the strain changes from 0 to 1000